Stochastic model for the geometrical rail track degradation process in the Portuguese railway Northern Line - Cecília Vale (2013)
The geometrical track degradation is characterized by the evolution over time (or tonnage) of several parameters such as the longitudinal level, the alignment, the gauge, the twist and the cross level. Dynamic track inspections allow monitoring the track geometrical quality which is essential to ensure track availability and reliability, passenger safety and comfort and also energy efficiency. The track geometrical quality is guaranteed by performing condition-based maintenance and renewal actions during the life of the track and for that it is crucial to understand the geometrical track degradation process. In this paper, a stochastic model for characterizing the geometrical track degradation process over time is presented. The Portuguese railway Northern Line is adopted as a case-study and a statistic analysis is performed for different vehicle speed groups, in accordance with CEN [1]. The new contribution of this research is that the Dagum distribution, usually adopted for representing the income distribution, may represent the geometrical track degradation process in terms of the longitudinal level.